ON THE PREDICTION ERROR - PEREIRA, Leandro da Silva; CHAVES, Lucas Monteiro; SOUZA, Devanil Jaques de (Brazilian Journal of Biometrics, 2019)
The theory of model prediction error is presented in details from the point of view of geometric constructions. It is expected that this approach can be a possible pedagogical tool in the treatment of the subject. Although the focus is essentially conceptual, all algebraic passages is developed in order to facilitate a greater understanding for the reader. Two elementary examples are presented..